2006
DOI: 10.1177/097325860500100103
|View full text |Cite
|
Sign up to set email alerts
|

Public Relations in India Review of a Programme of Research*

Abstract: Public relations in India has witnessed a significant growth since the early 1990s. Based on the combined research of both authors over a period of 13 years, this article provides a meta-analysis and tracks recent changes within the profession keeping in mind the reconfiguring economic, societal, political and global/ local climate, we focus in-depth on the impact of societal culture and media environment on public relations in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In the course, the references which research some of these topics, for example: PR manager career development (Wolf 2006), PR manager satisfaction (Abbott 2003), PR manager education and skills (Elliot et al 2003;Lubbers 2002). References which present other countries' experience in the field of PR (Arceo 2004;Bardhan et al 2006;Guth 2000;Taylor 2004) had important impact on creating the questionnaire, as well as the references by the authors who deal with PR in the conditions which are the subject of this paper ( or evi et al 2004;Filipovi /Kosti /Prohaska 2003;Sajfert/ or evi /Beši 2006). Presentation of the results and analysis for each group of question follows below.…”
Section: Characteristics Of the Researchmentioning
confidence: 99%
“…In the course, the references which research some of these topics, for example: PR manager career development (Wolf 2006), PR manager satisfaction (Abbott 2003), PR manager education and skills (Elliot et al 2003;Lubbers 2002). References which present other countries' experience in the field of PR (Arceo 2004;Bardhan et al 2006;Guth 2000;Taylor 2004) had important impact on creating the questionnaire, as well as the references by the authors who deal with PR in the conditions which are the subject of this paper ( or evi et al 2004;Filipovi /Kosti /Prohaska 2003;Sajfert/ or evi /Beši 2006). Presentation of the results and analysis for each group of question follows below.…”
Section: Characteristics Of the Researchmentioning
confidence: 99%
“…(3) formulating work programs of public relations and industry; (4) determining the implementation strategy of public relations and industry; (5) establishing procedures for the implementation of public relations and industry; (6) establishing evaluation standards for the implementation of public relations and industry; (7) carrying out of public relations and industry internally; (8) executing public relations and industry externally (community, BW IW); (9) evaluating the implementation of BW IW cooperation; (10) following up the evaluation of the implementation of BW IW cooperation; (11) entering into MoU with BW IW; and (12) enhancing cooperation with BW IW are valid variables in explaining the constructs of public and industrial relations management variables. It can be seen from the value of factor loads meet the acceptance criteria is λ ≥ 0.50.…”
Section: Conculsionmentioning
confidence: 99%
“…The status and structure of public relations in management at a modern company is a member of a policymaking team that runs the company's wheels. It cannot be denied, however, that public relations are on the minor side in terms of authority [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that, media relation was the primary focus of the public relations efforts of all the organizations. (Bardhan & Sriramesh, 2006) Another study by Seow Ting Lee and Mallika Hemant Desai studied on the media relations in 296 NGOs from India. The study found that "an organization's dialogic orientation has a positive impact on media relations knowledge and strategy but not on the action dimension that focuses on providing information subsidies to journalists."…”
Section: Indiamentioning
confidence: 99%